Análisis de contenido sobre el manejo ambiental de la quebrada de las abras en la plataforma digital de Diario La Prensa período julio- diciembre 2019 - Estrada Herrera, Erik Ramiro (2021)
ABSTRACT In this research work, the research problem was, how the information was processed in the digital edition of Diario La Prensa on Environmental Management of the Quebrada de las Abras, the work is supported by the bibliographic review of communication theories and journalistic genres as a product of analysis, using matrices of analysis of predesigned contents. The methodology of study was the analysis of the publications in the digital version of La Prensa newspaper through a detailed study, it was possible to know the criteria of the journalist to translate the information into the printed media, the tools of analysis used were the analysis of content and interviews with professionals specialized in environmental issues, the results gave us information on the type of journalistic genre that dominated in the publications on quebrada de Las Abras, its location, its origin, the elements of graphic support and the criterion of the journalist to express the news were also analyzed, taking as reference the elements of the discursive genre, such as the criterion of the journalist, the language used, the approach to which the news was directed, the sources used to corroborate the fidelity of the publication knowledge of the problem it exposes in the graphic media. Keywords: analysis, content, management, environmental, Las Abras, digital, Diario La Prensa. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301